Effect of lactoferrin in oral nutrition supplement (ONS) towards IL-6 and IL-10 in failure to thrive children with infection [version 1; peer review: 2 approved with reservations] - Widjaja, Nur Aisiyah; Hamidah, Azizah; Purnomo, Marissa Tulus; Ardianah, Eva (F1000 research, 2023)
Background: Growth failure due to infection in children is a major health problem throughout the world. It provokes a systemic immune response, with increased interleukin (IL)-6 and reduced IL-10. Lactoferrin (Lf) is a multifunctional iron-binding protein that can be found in whey protein inside formula milk such as oral nutrition supplement (ONS), which can upregulate anti-inflammatory cytokines (IL-10) and modulate pro-inflammatory cytokines. This study investigates the effect of Lf supplementation in ONS on IL-6 and IL-10 levels in children with failure to thrive and infection. Methods: We performed a quasi-experimental pre- and post-study in children aged 12-60 months old with failure to thrive due to infectious illness. The subjects received 400 ml of oral nutritional supplements (ONS, 1 ml equivalent to 1 kcal) each day for 90 days, and their parents received dietary advice and medication based on the underlying illness. Blood was drawn to measure IL-6 and IL-10 before and after the intervention. Results: There were 75 subjects recruited and divided into group-1 and group-2 based on age. The incidence of undernutrition was 37.33%. Lf in ONS intervention improved body weight and body length. Lf also reduced IL-6, although there was not a significant difference before and after the intervention. However, the IL-6 reduction was significantly higher in subjects with undernutrition compared with subjects with weight faltering. Pre-intervention IL-6 levels were higher in children with stunting than in children with normal stature. There was a greater change in IL-6 in children with severe stunting than in children with normal stature or stunting. IL-10 was significantly reduced after the intervention . Conclusions: In addition to improving body weight and length, Lf supplementation in ONS improved immune response homeostasis by balancing IL-6 and IL-10 levels and by improving the IL-6/IL-10 ratio. ClinicalTrials.gov number ID: NCT05289674, dated May 3 rd 2022.